A few remarks on the mutual relations between anthropology and history based on the book by Zbigniew Szmyt, Zbyt głośna historyczność. Użytkowanie przeszłości w Azji Wewnętrznej - Stobiecki, Rafał (A mosaic city: The culture-oriented description, 2023)
The article concerns the connections between anthropology and history. The author describes the opportunities and threats related to interdisciplinarity present in these two sciences, refering to the subject of research, types of sources, methodologies and expected research results. The basis for the considerations is book Zbyt głośna historyczność. Użytkowanie przeszłości w Azji Wewnętrznej [Too Loud a Historicity. The Usable Past in Inner Asia] by Zbigniew Szmyt.